H3K9 Methyltransferases Suv39h1 and Suv39h2 Control the Differentiation of Neural Progenitor Cells in the Adult Hippocampus - Guerra, Miguel V.; Cáceres, Matías I.; Herrera-Soto, Andrea; Arredondo, Sebastián B.; Varas-Godoy, Manuel; van Zundert, Brigitte; Varela-Nallar, Lorena (Frontiers in Cell and Developmental Biology, 2022)
In the dentate gyrus of the adult hippocampus new neurons are generated from neural precursor cells through different stages including proliferation and differentiation of neural progenitor cells and maturation of newborn neurons. These stages are controlled by the expression of specific transcription factors and epigenetic mechanisms, which together orchestrate the progression of the neurogenic process. However, little is known about the involvement of histone posttranslational modifications, a crucial epigenetic mechanism in embryonic neurogenesis that regulates fate commitment and neuronal differentiation. During embryonic development, the repressive modification trimethylation of histone H3 on lysine 9 (H3K9me3) contributes to the cellular identity of different cell-types. However, the role of this modification and its H3K9 methyltransferases has not been elucidated in adult hippocampal neurogenesis. We determined that during the stages of neurogenesis in the adult mouse dentate gyrus and in cultured adult hippocampal progenitors (AHPs), there was a dynamic change in the expression and distribution of H3K9me3, being enriched at early stages of the neurogenic process. A similar pattern was observed in the hippocampus for the dimethylation of histone H3 on lysine 9 (H3K9me2), another repressive modification. Among H3K9 methyltransferases, the enzymes Suv39h1 and Suv39h2 exhibited high levels of expression at early stages of neurogenesis and their expression decreased upon differentiation. Pharmacological inhibition of these enzymes by chaetocin in AHPs reduced H3K9me3 and concomitantly decreased neuronal differentiation while increasing proliferation. Moreover, Suv39h1 and Suv39h2 knockdown in newborn cells of the adult mouse dentate gyrus by retrovirus-mediated RNA interference impaired neuronal differentiation of progenitor cells. Our results indicate that H3K9me3 and H3K9 methyltransferases Suv39h1 and Suv39h2 are critically involved in the regulation of adult hippocampal neurogenesis by controlling the differentiation of neural progenitor cells.